Does working capital management affect the profitability of commercial banks: the case of Kosovo - Mazreku, Ibish; Morina, Fisnik; Zeqaj, Florentina (European Journal of Sustainable Development, 2020)
Purpose: This paper aims to analyze working capital and its impact on the profitability of commercial banks. The other objectives of this study are to analyze the factors that influence the profitability of commercial banks, to find out the relationship between profitability and working capital management. To achieve these research objectives, several research questions have been posited: How much does working capital affect the profitability of commercial banks? What are the relationships between bank profitability and bank size, debt ratio and current ratio? What are the other factors affecting the profitability of commercial banks? Methodology: The empirical data to be used in this research are secondary data and will be based on annual reports of commercial banks and reports of the Central Bank of Kosovo. From these data, some indicators such as return on assets, current ratio, debt ratio and banks’ size will be calculated. This research covers a period of 5 years and the data will be analyzed and interpreted through econometric models. In addition, to analyze the impact of working capital on the profitability of commercial banks in Kosovo, trend analysis will also be applied through the comparative method. Findings: Based on the empirical results, we can conclude that bank size and the current ratio have positively affected the performance of commercial banks in Kosovo, whereas the debt ratio has had a negative effect. All the independent variables in relation to the dependent variable (ROA) are at the standard level of significance P-value = 0.05. Practical implications: Through this study we can recommend all commercial banks in Kosovo to invest much more in working capital, since financial investments in working capital affect the bank’s profitability. This means that a high investment in the elements of working capital can lead to increased bank profitability, whereas its profitability decreases when investment in working capital is low. Originality: This paper presents real and sustainable results with respect to the conclusions. The period analyzed (2013-2017) is a persuasive period for drawing competent conclusions and recommendations. Keywords: working capital, debt ratio, current ratio, bank size, return on assets JEL Classification: G2, G20, G21, G3, G32, D24